2015
DOI: 10.1167/15.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual enhancement prior to intended and involuntary saccades

Abstract: Prior to an eye movement, attention is gradually shifted toward the point where the saccade will land. Our goal was to better understand the allocation of attention in an oculomotor capture paradigm for saccades that go straight to the eye movement target and for saccades that go to a distractor and are followed by corrective saccades to the target (i.e., involuntary saccades). We also sought to test facilitation at the future retinotopic location of target and nontarget objects, with the principal aim of veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…Our results relate to earlier findings by Puntiroli et al (2015), who tested the allocation of attention at targets and non-targets while making voluntary and involuntary saccades. In their experiment participants made either one or two saccades.…”
Section: Discussionsupporting
confidence: 90%
“…Our results relate to earlier findings by Puntiroli et al (2015), who tested the allocation of attention at targets and non-targets while making voluntary and involuntary saccades. In their experiment participants made either one or two saccades.…”
Section: Discussionsupporting
confidence: 90%
“…Since the target was very difficult to detect and required a high degree of attention toward the particular location, the authors proposed that attention, rather than feature information, is predictively remapped prior to a saccade. This hypothesis was further supported by several subsequent studies (Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015). However, in recent years a number of studies have provided evidence that feature information, in addition to attentional pointers, is also involved in transsaccadic remapping (Cha & Chong, 2013;Demeyer, De Graef, Wagemans, & Verfaillie, 2009, 2010Demeyer, Graef, Verfaillie, & Wagemans, 2011;Eccelpoel, Germeys, Graef, & Verfaillie, 2008;Edwards, VanRullen, & Cavanagh, 2017;Fracasso, Caramazza, & Melcher, 2010;Gordon, Vollmer, & Frankl, 2008;Habtegiorgis, Rifai, Lappe, & Wahl, 2018;Harrison & Bex, 2014;Hayhoe, Lachter, & Feldman, 1991;He et al, 2017;Herwig & Schneider, 2014;Koller & Rafal, 2018;Melcher, 2007;Nakashima & Sugita, 2017;Oostwoud Wijdenes, Marshall, & Bays, 2015;Paeye, Collins, & Cavanagh, 2017;Prime, Niemeier, & Crawford, 2006;Prime, Vesia, & Crawford, 2011;Sligte et al, 2017;Wittenberg, Bremmer, & Wachtler, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013;Zimmermann et al, 2017;…”
Section: Remapping Of Features or Attentional Pointers?mentioning
confidence: 73%
“…Previous studies have shown that spatial attention rapidly selects saccade targets before the onset of the movement (Castet et al, 2006;Deubel, 2008;Rolfs & Carrasco, 2012) and that feature information such as motion survives the saccade (Fallah & Reynolds, 2012). Due to the retinotopic organization of the visual-processing machinery, spatial attention requires an updating process that remaps the attentional landscape each time we execute a saccade (Cavanagh et al, 2010;, and this remapping of attention has received considerable empirical support Puntiroli et al, 2015;Rolfs et al, 2011;Szinte et al, 2015). In contrast to that, FBA is independent of space, and exerts its effects broadly across the visual field (White & Carrasco, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has accumulated that the allocation of spatial attention before saccades plays a key role in perceptual continuity across saccades-that is, the visual system's ability to deal with the massive displacement of objects on the retina that saccades unavoidably entail (Cavanagh, Hunt, Afraz, & Rolfs, 2010;Rolfs, 2015). An instant before the execution of a saccade, attention shifts towards the future retinal locations of currently attended objects (Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015;Rolfs et al, 2011;Szinte, Carrasco, Cavanagh, & Rolfs, 2015;Szinte, Jonikaitis, Rolfs, Cavanagh, & Deubel, 2016). This remapping of attention has been associated with benefits in visual processing at these locations after saccade landing and the facilitation of secondary saccades toward them (Puntiroli et al, 2015;Rolfs et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation